Trastuzumab-induced human cardiomyocyte damage through the Notch2/JAK2/STAT3 pathway - Su, Zhenbo; Liu, Siyao; Zou, Yinggang; Shan, Liang; Yu, Miao; Xie, Shishun; Li, Xiangjun; Jin , Ying (Clinics, 2023)
Objective:Trastuzumab is the preferred drug for the treatment of breast cancer. However, research on the cellular mechanisms of trastuzumab's potential cardiotoxicity is insufficient. The purpose of this study was to explore the toxic effects and potential mechanism of action of trastuzumab on cardiomyocytes. Method: Human Cardiomyocyte (HCM) viability was assessed using the MTT method. HCM apoptosis was detected using the Hoechst33342/PI Fluorescent staining. The LDH and CK activities of the cell were measured using commercially available LDH and CK assay kits. The expression levels of Notch2, JAK2, STAT3, cleaved caspase 3, bax, and bcl 2 in HCMs were detected using western blotting. Results: The results showed that 250 mg/L trastuzumab induced cardiomyocyte injury and apoptosis, inhibited viability, activated the Notch2 receptor, and inhibited JAK2/STAT3 expression in HCM. Inhibition of Notch2 expression in HCM by targeted siNotch2 transfection reversed the trastuzumab-induced injury and apoptosis, and the expression of JAK2/STAT3 returned to normal levels. Conclusions: Trastuzumab induces Notch2 expression by inhibiting the JAK2/STAT3 pathway of HCMs, promotes cell apoptosis, and causes cardiomyocyteinjury. Notch2 may be a potential target of trastuzumab-inducedmyocardial injury. This experiment reveals the mechanism of trastuzumab-induced cardiotoxicity, providing a theoretical basis for the application of trastuzumab.